Functional connectivity of the amygdala and the antidepressant and antisuicidal effects of repeated ketamine infusions in major depressive disorder - Liu, Haiyan; Wang, Chengyu; Lan, Xiaofeng; Li, Weicheng; Zhang, Fan; Fu, Ling; Ye, Yanxiang; Ning, Yuping; Zhou, Yanling (Frontiers in Neuroscience, 2023)
Background: Dysfunction of the amygdala is the core pathogenesis of major depressive disorder (MDD). However, it remains unclear whether ketamine treatment could modulate characteristics of amygdala-related networks. We aimed to explore the relationship between changes in the resting-state functional connectivity (RSFC) of the amygdala and the treatment of ketamine in MDD and to identify important neuroimaging predictors of treatment outcome. Method: Thirty-nine MDD patients received six subanesthetic dose infusions of ketamine. Depressive and suicidal symptoms were assessed and magnetic resonance imaging (MRI) scans were performed before and after six ketamine infusions. Forty-five healthy controls also underwent once MRI scans. Seed-based RSFC analyses were performed, focusing on the bilateral amygdala. Result: After ketamine treatment, the RSFC between the left amygdala (LA) and the left medial superior frontal gyrus (mSFG) of MDD patients enhanced significantly, and this change was positively correlated with the reduction in depressive symptoms（r = 0.40, p = 0.012). The combination baseline RSFC of LA - right putamen and right amygdala (RA) - right putamen was related to the antidepressant and antisuicidal effects of ketamine. The combination baseline RSFC of LA - right putamen and RA - right putamen could predict the ineffective antidepressant (AUC = 0.739, p = 0.011) and antisuicidal effects of ketamine (AUC = 0.827, p = 0.001). Conclusion: Ketamine can regulate the relevant circuits of amygdala and mSFG, and the baseline RSFC between bilateral amygdala and right putamen may be a predictor of the response of ketamine’s antidepressant and antisuicidal treatment.